Temperature effect analysis on magneto-rheological damper’s performance - Mohammad Meftahul , Ferdaus; Rashid, Muhammad Mahbubur; H., Muhammad; Md. Yosuf, Hazlina; Bhuiyan , M. M. I.; AlraddadiAbdulaziz, Abdulaziz (Engineering and Technology Publishing, 2014)
Magnetorheological (MR) damper is one of the most advanced applications of semi active damper in controlling vibration. Its use is increasing day by day in the vehicle suspension system due to its continuous controllability in both on and off state. MR damper’s damping force can be controlled by changing the viscosity of its internal magnetorheological fluids (MRF). Applying an external magnetic field viscosity of MRF can be controlled. Electromagnet such as solenoid coil is normally used as external magnetic field source. These coils are attached inside the damper’s piston head. When the damper operates these coils create heat. That’s why the conventional MR dampers normally face wide variations in temperature. This change of temperature results decay in MRF viscosity as well as post-yield damping of the damper. In this paper temperature effect on MR fluids viscosity and on MR dampers performance represented analytically and experimentally. Due to this temperature effect the deviation of MR dampers performance has shown here experimentally. Also a novel technique for solving the problem explained clearly.